The mototaxis of Peru and the contradictions of «(in)formality» and «modernity» - Boose, William (2022)
This article offers an ambitious, though still fragmented, history of motorcycle taxis in Peru. It offers three central arguments. First, it highlights that motorcycle taxi drivers have played a fundamental role in the production of urban space.Second, it argues that state, elite, and popular discourses about «informality» and the «modern city» stigmatize motorcycle taxi drivers in ways that are classist and racialized, targeting them for strict policing. Finally, it suggests that if we think with motorcycle taxi drivers and the materiality of motorcycle taxis, we can reveal the contradictions inherent to the «formal»-«informal» and «modern»- «non-modern» binaries and thus more lucidly analyze urban space and relations.